Maternal Anemia is Associated with Depressive Symptoms in the First Two Years of Postpartum in Indonesia (Proceedings of the International Conference on Public Health, 2019)
Becoming a mother is a normal women phase, but it needs cognitive and adaptive behavior. Some women have difficulties passing this phase and develop depressive symptoms. Also, anemia postpartum is a global public health problem. This study was to examine the association between anemia and maternal depressive symptoms. This study is a cross-sectional study and used data from the fifth wave of the Indonesia Family Life Survey (IFLS). The unit of analysis is ever-married women and gave the last birth in recent two years preceding the survey. Depressive symptoms were measured by CESD-10. A CESD-10 total score of ten or more indicates that there are any depressive symptoms. Anemia was defined by hemoglobin concentration below 12 g/dl. Logistic regression was performed to determine the association between anemia and depressive symptoms after controlling for potential confounders. Anemia was significantly associated with depressive symptoms. Women with anemia were 1.32 times more likely to have depressive symptoms than non-anemic women. It is crucial to screen depressive symptoms and anemia in the postpartum period. Since anemia and maternal depressive symptoms were associated, maternal-focused interventions are suggested to reduce both maternal anemia and depressive symptoms in the first two years postpartum.
Keywords: depressive symptoms, anemia, center of epidemiological studies depression, hemoglobin